Influence of abutments surface (machined vs. laser-microgrooved) in soft-tissue response during one year of function : clinical and biochemical outcomes of a RCT with split-mouth design = Influencia de la superficie de los pilares (mecanizada versus microranurada con láser) en la respuesta del tejido blando durante un año de función : resultados clínicos y bioquímicos de un ECA con diseño de boca dividida - Guarnieri, Renzo
The purpose of this study was to evaluate peri-implant soft tissue response by assessing IL-6, IL-1b and MMP-8 levels in peri-implant crevicular fluid (PICF) around machined vs. laser-microgrooved implants/healing/prosthetic abutments during 1 year of function. Twenty-four patients each received 2 one-stage implants in a split mouth design on the same jaw. In each patient, one implant, one immediate healing, and one prosthetic abutment with a machined surface (M group), and one implant, one immediate healing abutment and one prosthetic abutment with a laser-microgrooved surface (LMS group) were used. PICF sampling, pocket probing depths (PPD) and bleeding on probing (BOP) were assessed at 1, 3, and 12 months. IL-6, IL-1b and MMP-8 levels were determined by specific enzyme-linked immunosorbent assay systems (ELISA). Repeated measure ANOVA was used to run comparisons with groups and between groups months at 1, 3, and 12 months. At 3 and 12 months, the LMS group showed significantly lower PD, BOP and IL-6, IL-1β and MMP-8 levels than the M group (P<.05). This study suggests the presence of more remodeling and/or inflammatory phenomena around implants/abutments with a machined surface than around implants/abutments with a laser-microgrooved surface.